Victorias secret : keeping up in a changing industry - Robson, Karen; Pitt, Leyland (London : SAGE Publications: SAGE Business Cases Originals, 2018)
Victorias Secret, a powerful player in the womens undergarment industry, built a highly sexual brand image around tall, thin models. In 2017 the company remained the dominant player in the industry, but the brand faced increasing pressure from new competitors, as well as changing customer preferences. The company responded by cutting non-core product lines and adapting its marketing strategy, but it was not clear whether these changes were moving the company in the right direction. This case explores how changes to the marketing environment impact brands, even those as big and powerful as Victorias Secret. In addition, this case explores how a brand can adapt to changes in the industry landscape.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Victoria's Secret (Firm); Lingerie; Clothing and dress